STUDI KASUS : EFEKTIVITAS TERAPI LATIHAN ACTIVE CYCLE OF BREATHING TECHNIQUE (ACBT) PADA ASMA BRONKIAL - Iftitah Rahmawati Syafriningrum; Nanang Heru Sumarsono (Jurnal Ilmiah Fisioterapi, 2023)
Background : Asthma is a condition in which people with overactive airways experience cough, shortness of breath and reversible airways. Asthma affects more than 5% of the world's population, and some indicators show that its prevalence is increasing. In general, the treatment of asthma bronchial is divided into two parts, namely pharmacological and non-pharmacological. One of the non-pharmacological treatments for asthmatic patients is the Active Cycle of Breathing Technique (ACBT), which consists of Breathing Control (BC), Thoracic Expansion Exercise (TEE), and Forced Expiration Technique (FET). Research Methods : The research method is experimental, case studies are used in the research design, and data collection techniques are used Pre and Post drops. The sampling technique is random sampling. Examination of dyspnea from respiratory rate and borg scale, while for examination of thorax expansion using the mid line. Result : After doing therapy 3 times, there was a decrease in shortness as evidenced by the Borg scale from a scale of 5 to a scale of 3, a decrease in respiratory rate from 28 to 23 and measurements of thorax expansion which showed a difference in increase. Conclution : Based on these results, it can be concluded that physiotherapy intervention with ACBT exercise therapy is effective in bronchial asthma patients.